Automated Sequence Preprocessing in a Large-Scale Sequencing Environment - Wendl, Michael C. (Cold Spring Harbor Laboratory Press, 1998)
A software system for transforming fragments from four-color fluorescence-based gel electrophoresis experiments into assembled sequence is described. It has been developed for large-scale processing of all trace data, including shotgun and finishing reads, regardless of clone origin. Design considerations are discussed in detail, as are programming implementation and graphic tools. The importance of input validation, record tracking, and use of base quality values is emphasized. Several quality analysis metrics are proposed and applied to sample results from recently sequenced clones. Such quantities prove to be a valuable aid in evaluating modifications of sequencing protocol. The system is in full production use at both the Genome Sequencing Center and the Sanger Centre, for which combined weekly production is ∼100,000 sequencing reads per week.